The Effectiveness of Instagram-Based Hortatory Exposition Texts on Students’ Reading Comprehension - Sugiarto, Aprilliya Indah; Wicaksono, Agung; Khoiriyah, Khoiriyah (UICELE, 2026)
This study investigated the effectiveness of Instagram-based hortatory exposition texts in improving the reading comprehension of eleventh-grade students at SMAN 7 Kediri in the academic year 2025/2026. The study focused on four indicators of reading comprehension: identifying main ideas, supporting details, inferences, and understanding vocabulary in context. This research employed a quantitative approach using a pre-experimental one-group pre-test and post-test design. The participants were 24 eleventh-grade students selected through random sampling. The instruments used in this study were reading comprehension tests and a questionnaire. The data were collected through administering the pre-test, post-test, and questionnaire, and then analyzed using a paired sample t-test. The findings showed that students’ reading comprehension improved significantly after the implementation of Instagram-based hortatory exposition texts. The mean score increased from 56.87 in the pre-test to 84.37 in the post-test, while the significance value was 0.000, which was lower than 0.05. In addition, the questionnaire results showed positive students’ behavior toward the use of Instagram in reading activities, particularly in identifying inferences. However, this study was limited to one class and focused only on reading comprehension. Therefore, future researchers are suggested to involve larger samples and different research designs to obtain broader findings.